Electroencephalography - Sittiprapaporn, Phakkharawat (IntechOpen, 2017)
This edited volume Electroencephalography is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of medicine and health sciences. The book comprises single chapters authored by various researchers and edited by an expert active in the electrophysiological monitoring method research area. Each chapter is complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on electrophysiological monitoring method and opens new possible research paths for further novel developments.